The Role of Internet Exchange Points in Broadband Policy and Regulation - Cavalcanti, Daniel Brandão (Law, State and Telecommunications Review, 2011)
New investments in Internet backbone infrastructure and the need to exchange traffic with existing backbones, on a peering or transit basis, point to the emergence of a key infrastructure element ”“ the Internet Exchange Point (IXP). There are very few IXPs available today, considering the huge increase in the number of autonomous systems advertised. IXPs deployed by research networks demonstrate that a substantial increase in their number would improve the Internet topology, increase connectivity, reduce latency and the cost of traffic exchange. Additionally, IXPs can be efficient locations from which to offer system services. This paper discusses possibilities of regulatory action to stimulate the implementation of IXPs and to ensure that their benefits are widely shared.